2017
DOI: 10.3389/fenvs.2017.00063
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Tissue accumulation of microplastics in mice and biomarker responses suggest widespread health risks of exposure

Abstract: Citation:Tang BL (2017) Commentary: Tissue accumulation of microplastics in mice and biomarker responses suggest widespread health risks of exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…2,11,12 Nevertheless, the great majority of studies are stating the highest concentrations typically found are in the range of less than 1 to 10s of particles per meter squared (i.e., 1000 L). 2,3,7,8,13,14 These concentrations are several orders of magnitude lower than virtually all laboratory studies and organisms feeding on this sized range will find orders of magnitude more plankton available for ingesting. Also, many of the studies measure concentrations based on mass (e.g., mg/L) or surface area (number/km 2 ), and these units add large uncertainty to actual organism exposures to these diverse particles.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…2,11,12 Nevertheless, the great majority of studies are stating the highest concentrations typically found are in the range of less than 1 to 10s of particles per meter squared (i.e., 1000 L). 2,3,7,8,13,14 These concentrations are several orders of magnitude lower than virtually all laboratory studies and organisms feeding on this sized range will find orders of magnitude more plankton available for ingesting. Also, many of the studies measure concentrations based on mass (e.g., mg/L) or surface area (number/km 2 ), and these units add large uncertainty to actual organism exposures to these diverse particles.…”
mentioning
confidence: 85%
“…As an environmental toxicologist and risk assessor, I knew low microplastic exposure concentrations dictated there could be no risk. Thankfully, others are now beginning to join this chorus. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the studies performed thus far suggest that, after MP exposure, a collective increase in various metabolites occurs rather discrete changes to a few individual metabolites. This could suggest a general disturbance of cellular function rather than specific effects due to the interaction of the MPs with a distinct cellular process, as discussed by some authors (Mattsson et al, 2015;Tang, 2017). Indeed, Tang (2017) proposed that metabolic alterations may have limited specific relevance and support more the notion of broad inflammatory responses or alterations to nutrient uptake and assimilation.…”
Section: Discussionmentioning
confidence: 96%
“…This could suggest a general disturbance of cellular function rather than specific effects due to the interaction of the MPs with a distinct cellular process, as discussed by some authors (Mattsson et al, 2015;Tang, 2017). Indeed, Tang (2017) proposed that metabolic alterations may have limited specific relevance and support more the notion of broad inflammatory responses or alterations to nutrient uptake and assimilation. Changes observed in the brain metabolite profile could also possibly arise from broad effects related to nutrition.…”
Section: Discussionmentioning
confidence: 96%